The 3D Nuclide Chart. (December 2020) - Simpson, E. C.
Abstract: We present an overview of The 3D Nuclide Chart, a new online nuclide chart designed for producing high quality 3D nuclide chart images for use in publications, presentations, education and outreach. An historical overview of the design of nuclide charts is given, followed by a description of The 3D Nuclide Chart itself.